1997
DOI: 10.1073/pnas.94.9.4664
|View full text |Cite
|
Sign up to set email alerts
|

Ultrarapid, highly efficient viral gene transfer to the heart

Abstract: Gene therapy for common myocardial diseases will require effective and homogeneous gene delivery throughout the intact heart. We created two experimental models to identify and optimize parameters important for adenovirus-mediated cardiac gene transfer. In cultured rabbit ventricular myocytes, the percentage of infected cells increased with higher absolute numbers of virus particles, longer durations of virus exposure, physiological temperatures, and specific culture media compositions. Simulating the in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0
3

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(121 citation statements)
references
References 12 publications
2
116
0
3
Order By: Relevance
“…When the duration of virus recirculation was increased to 20 min, the transfection efficiency increased to 40%. 10 These results are also in keeping with a more recent study by Logeart et al 18 Thus, it is likely that gene delivery in vivo would be less efficient due to the presence of blood, and that only one pass through the coronary circulation is unlikely to allow significant transfection.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…When the duration of virus recirculation was increased to 20 min, the transfection efficiency increased to 40%. 10 These results are also in keeping with a more recent study by Logeart et al 18 Thus, it is likely that gene delivery in vivo would be less efficient due to the presence of blood, and that only one pass through the coronary circulation is unlikely to allow significant transfection.…”
Section: Discussionsupporting
confidence: 79%
“…9 by oxygenated perfluorocarbon emulsion as viral diluent Further understanding of the factors involved in gene transfer by intracoronary delivery of recombinant adenovirus has been gained through a series of experiments involving Langendorff perfusion. 10,11 These studies show that the coronary flow rate, absolute amount of virus, time spent in the coronary circulation and composition of perfusate were major factors affecting intracoronary gene transfer 10 and increasing capillary permeability leads to improvements in gene transfer efficiency. 11 A related model of intracoronary gene delivery has confirmed feasibility provided transcapillary pressure is increased by simultaneous occlusion of the aorta and pulmonary artery in the rat, 12 and more recently, the rabbit.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34] The higher efficiency of viral vectors at delivering genes in vivo than nonviral vectors is illustrated by a direct comparison in which luciferase transgene activity was 10-fold higher in rat cardiac grafts transduced with an adenoviral vector compared with a plasmid vector. 35 None the less, even with viral vectors, investigators have documented inefficient gene transfer by allograft perfusion, with most studies reporting less than 1% of the cells expressing the transgene.…”
Section: Figure 4 Prolonged Survival Of Vil-10 Transduced Allografts mentioning
confidence: 99%
“…19 Moreover, the replacement of the blood by a crystalloid solution may also have enhanced vascular permeability. 17 Using our protocol to block the aortic outflow and the right atrial inflow, we were able to mimic under closechest conditions the protocol previously developed by Hajjar et al 7 These authors used cross-clamping of the aorta and the pulmonary artery to perform adenoviral transfection under HIP. 4,7 We found that injection of adenoviral vectors within a short period (20 s) into the aortic root without cardiac arrest resulted in aortic root pressures above 300 mmHg but yielded only sparse and uneven gene transduction of the myocardium (3-5% of CMs).…”
Section: Optimization Of Gene Deliverymentioning
confidence: 98%
“…Given the size of adenoviral particles (73 nm), which is too large to pass the normal endothelial barrier, disruption of the endothelial tight junction seemed to be a prerequisite to ensure access of the virus to the interstitium. 12 Therefore, factors capable of increasing endothelial permeability such as histamine, 3,13 bradykinin and serotonin 17 also improve gene transduction in the isolated hearts and in vivo. Surprisingly, pretreatment of coronary vessels with the nitric oxide (NO) donor SNAP or histamine, substances well known to elevate vascular permeability, did not increase the transfection rate in our study.…”
Section: Optimization Of Gene Deliverymentioning
confidence: 99%